Hubungan Body Image dan Psychological Well-Being Pada Perempuan Dewasa Awal Pengguna Instagram - Narotin, Narotin; Satwika, Yohana Wuri (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Social media, especially Instagram, has become a very popular platform among early adult women. Instagram is often used to share photos and videos, which can affect a person's perception of his or her physical appearance or body image. This study aims to determine how much the relationship between Body Image and psychological Well-being in early adult female Instagram users. The approach used in this study is quantitative correlational. The sampling technique used is purposive sampling technique involving early adult women aged 18-25 years who are domiciled in the city of Surabaya with a total of 100 people. The instruments used in this study are body image scale and psychological well-being scale. The data analysis technique used in this study is a pearson product moment correlation with the help of SPSS 26.0 for windows. The results showed a correlation of r=0.825 with a degree of significance of 0,000<0.05 which means there is a significant relationship between body image and psychological well-being.